Hybrid learning : innovation in educational practices : 8th International Conference, ICHL 2015, Wuhan, China, July 27-29, 2015, Proceedings /: innovation in educational practices : 8th International Conference, ICHL 2015, Wuhan, China, July 27-29, 2015, Proceedings. (2015) - Unknown
No abstract available